2019
DOI: 10.17509/ijpe.v3i2.21765
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Media Pembelajaran IPA Berbasis Powerpoint di Sekolah Dasar

Abstract: This research including development research (Research and Development) aims to develop powerpoint-based learning media. The subjects in this study were students and fifth grade teachers of SD Negeri Gaddong I, Bontoala, Makassar. The development model used in this study is the Dick & Carey development model which consists of 5 stages: (1) the needs analysis phase, (2) the product development design stage, (3) the product development stage, (4) the product evaluation and revision stage , (5) Final product. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
18

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 0 publications
0
12
0
18
Order By: Relevance
“…In addition, the use of powerpoints and infographics is very helpful to develop imagination and creativity, especially with attractive illustrations. Using powerpoint-based learning media, students can see directly the material presented by the teacher so that students can more easily understand the learning material [10]. Based on this explanation, it can be concluded that the use of powerpoint learning media, and infographics is very helpful in increasing the understanding of 6th-grade elementary school students.…”
Section: Pre-test and Post-test Resultsmentioning
confidence: 94%
“…In addition, the use of powerpoints and infographics is very helpful to develop imagination and creativity, especially with attractive illustrations. Using powerpoint-based learning media, students can see directly the material presented by the teacher so that students can more easily understand the learning material [10]. Based on this explanation, it can be concluded that the use of powerpoint learning media, and infographics is very helpful in increasing the understanding of 6th-grade elementary school students.…”
Section: Pre-test and Post-test Resultsmentioning
confidence: 94%
“…Penggunaan media pembelajaran dalam proses pembelajaran akan membantu peran guru dalam mengajar di kelas. Media sangat berguna dan sangat bermanfaat pada proses pembelajaran karena media dapat menjadikan proses pembelajaran lebih terarah, teratur, serta memiliki pedoman sesuai dnegan tujuan pembelajaran (Irfan et al, 2019;Salmiah et al, 2016). Media pembelajaran digunakan agar dapat mencapai tujuan pembelajaran dan menarik minat siswa (Arham & Dwiningsih, 2016;Ritonga et al, 2020).…”
Section: Pendahuluanunclassified
“…Temuan ini diperkuat dengan temuan yang menyatakan media power point sangat efektif dalam penyampaian sebuah materi (Astiti et al, 2021). Selain itu, penggunaan media pembelajaran berbantuan power point dapat menarik perhatian dan meningkatkan motivasi belajar siswa (Irfan et al, 2019). Media pembelajaran melalui power point juga dapat menarik minat siswa untuk fokus belajar dan dapat memperjelas materi pembelajaran sehingga dapat membantu siswa memahami konsep materi pembelajaran dan dapat meningkatkan hasil belajar siswa (Nurhidayati et al, 2019).…”
Section: Pembahasanunclassified
“…Bahkan, video dapat mendukung gaya belajar yang berbeda, khususnya siswa yang pembelajar visual. Proses pembelajaran dengan memanfaatkan media video animapoint berbasis masalah mampu meningkatkan motivasi siswa dalam belajar karena dalam media tersebut terdapat gambar, video, serta masalah yang disajikan dengan manarik, sehingga dapat melatih siswa dalam hal melihat, mendengar, dan mempraktikkan apa yang dipelajarinya (Astuti, Dewati, Okyranida, & Sumarni, 2019;Irfan, Muhiddin, & Ristiana, 2019). Temuan ini diperkuat dengan temuan sebelumnya yang menyatakan bahwa media video pembelajaran efektif digunakan dalam proses pembelajaran (Luhulima et al, 2017;Ponza et al, 2018).…”
Section: Pembahasanunclassified